RANCHING WITH WOLVES: REDUCING CONFLICTS BETWEEN LIVESTOCK AND WOLVES THROUGH INTEGRATED GRAZING AND WOLF MANAGEMENT PLANS (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} P rior to European contact, an estimated 60 million bison roamed the great grasslands and plains of North America, and over 200,000 wolves followed closely on their heels. Nowhere else was there such a concentration of prey and wolves. Since the coming of “civilized” man to the West, bison that had co-existed with and abundantly supported Native American tribes for perhaps thousands of years were destroyed in less than 150 years and replaced largely by livestock. This shift to a livestock culture in the West also resulted in the deliberate extermination of wolves from the lower forty-eight states.